Salicylic acid regulates PIN2 auxin transporter hyperclustering and root gravitropic growth via Remorin‐dependent lipid nanodomain organisation in Arabidopsis thaliana. Issue 2 (30th September 2020) - Ke, Meiyu; Ma, Zhiming; Wang, Deyan; Sun, Yanbiao; Wen, Chenjin; Huang, Dingquan; Chen, Zichen; Yang, Liang; Tan, Shutang; Li, Ruixi; Friml, Jiří; Miao, Yansong; et al.
Summary: To adapt to the diverse array of biotic and abiotic cues, plants have evolved sophisticated mechanisms to sense changes in environmental conditions and modulate their growth. Growth‐promoting hormones and defence signalling fine tune plant development antagonistically. During host–pathogen interactions, this defence–growth trade‐off is mediated by the counteractive effects of the defence hormone salicylic acid (SA) and the growth hormone auxin. Here we revealed an underlying mechanism of SA regulating auxin signalling by constraining the plasma membrane dynamics of PIN2 auxin efflux transporter in Arabidopsis thaliana roots. The lateral diffusion of PIN2 proteins is constrained by SA signalling, during which PIN2 proteins are condensed into hyperclusters depending on REM1.2‐mediated nanodomain compartmentalisation. Furthermore, membrane nanodomain compartmentalisation by SA or Remorin (REM) assembly significantly suppressed clathrin‐mediated endocytosis. Consequently, SA‐induced heterogeneous surface condensation disrupted asymmetric auxin distribution and the resultant gravitropic response. Our results demonstrated a defence–growth trade‐off mechanism by which SA signalling crosstalked with auxin transport by concentrating membrane‐resident PIN2 into heterogeneous compartments.